Attitudes and skills of Hong Kong Chinese medicine practitioners towards computerization in practice a cluster analysis. - Fai Chan, Moon (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
The objective was to determine whether definable subtypes exist within a cohort of Hong Kong Chinese medicine practitioners (CMPs) as related to computer use in their clinical practices absed on their skills, attitudes and background factors. Data were collected using a structured questionnaire. The sample of 954 CMPs was recruited in Hong Kong. The study employs personal and demographic variables, attitudes and a skills scale. A cluster analysis yielded three clusters. Each cluster represents a different profile of Hong Kong CMPs on computer use in their clinical practices. A clear profit of Hong Kong CMPs may benefit healthcare professionals in appropriate education or assistance to prompt the use of computers by CMPs, an officially recognized profession.